Hubungan Umur, Anemia, dan Usia Kehamilan dengan Kejadian KPSW Di Rumah Sakit TK. IV DR. Noesmir Baturaja Tahun 2021 - Fitri Yanti; Rohaya Rohaya; Eka Rahmawati (Universitas Batanghari Jambi, 2022)
Premature Rupture of Membranes (PROM) is the rupture of the fetal membranes before the onset of labor. World Health Organization (WHO) estimates that every year, there are more than 585.000 mother’s death in the world during their pregnancy or when delivering the baby. The number of PROM incidence in the world reaches 12,3% from the total number of labors. This study was aimed to find out the correlation between age, anaemia and gestational age with the incidence of Prematur Rupture of Membranes (PROM) in Obtetrics and Gynecology Ward of Inpatient Installation at Level IV Hospital of Dr. Noesmir Baturaja Year 2021. This study applied survey analytical method using cross sectional approach. The population of this study was taken from all maternity mothers in Obtetrics and Gynecology Ward of Inpatient Installation at Level IV Hospital of Dr. Noesmir Baturaja Year 2021with a total 324 mothers. 76 samples were taken by applying systematic random sampling method, the result of statistic test using chi-square showed that there was a significant correlation between mother’s age and the incidence of PROM with P-Value = 0,001 (≤ 0,05). The analysis of anaemia and the incidence of PROM with P-Value = 0,042 (≤ 0,05). The analysis of gestational age and the incidence of PROM with P-Value = 0,780 (≤ 0,05). This study can be used as the reference to add insight and skills for readers and a reference to improve the quality of services in hospitals.